TUNJUK AJAR DALAM UPACARA PERKAWINAN SUKU BATAK SIMALUNGUN - Grace Agustina; Syafrial Syafrial; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research titled Learning Point in Simalungun Batak Marriage Ceremony. This research aims to understand clearly point to teach conveyed in the execution of the wedding ceremony of the indigenous Batak Simalungun. This type of research is qualitative research with an ethnographic approach. The end result of this research is a descriptive narrative that is thoroughly accompanied interpretation that interpret the entire aspects of the culture. In accordance with these characters, this research seeks to obtain information that is as complete as possible about the execution of the wedding ceremony Batak Simalungun, from Partuha Maujana Simalungun (PMS) in Simalungun Country. The data in this research is pointing to verbal and non verbal learning in the implementation pekawinan Batak Simalungun. The validity of the data obtained by the technique of triangulation. Then, the data were analyzed by identifying and classifying based on the stage of the wedding ceremony. Results of the study, found the top ajar in Simalungun Batak marriage ceremony amounted to 83, Division of data the data i.e. (1) non verbal learning point shaped totaled 54 data, and (2) verbal learning point shaped totaled 29 data.Key Words: Learning, Pointing to the Wedding Ceremony, Batak Simalungun